A high light-shielding heat-shrinkable composite film and preparation method thereof

By using bidirectional stretching and modifier technology in the heat shrink composite film, the light shielding, barrier properties and puncture resistance of the PETG composite film are improved, and the problem of insufficient performance of the existing composite film is solved, and high light shielding and waterproofing are achieved and puncture-resistant packaging effect.

CN118810184BActive Publication Date: 2024-12-31ZHUHAI DOUMEN LIANBANG COLOR PLASTIC PRINT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410887849.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-03
Publication Date
2024-12-31
Estimated Expiration
2044-07-03

AI Technical Summary

Technical Problem

The light-shielding performance, barrier properties and puncture resistance of existing heat-shrinkage composite films are insufficient, making it difficult to meet the needs of packaging products for high light-shielding, waterproof and puncture resistance.

Method used

PETG is used as the main material, and the PETG molecular chains are arranged in aligned manner through bidirectional stretching, combining modifiers in the surface, intermediate and inner layer melt such as alkenyl modified calcium carbonate/carbon black, alkenyl modified montmorillonite /Carbon black and alkenyl modified carbon black are prepared by stirring, dropwise addition and reaction to prepare the surface, intermediate and inner layer melts to form a high light-shielding heat shrinkage composite film.

Benefits of technology

It significantly improves the light-shielding, barrier properties and puncture resistance of the composite film, improves the heat shrinkage performance of PETG, and meets the packaging needs of high light-shielding, waterproof and puncture-resistant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118810184B_ABST
    Figure CN118810184B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of composite film materials, and specifically discloses a high light-shielding heat-shrinkable composite film and a preparation method thereof. The high light-shielding heat-shrinkable composite film comprises a surface layer, an intermediate layer and an inner layer, and adopts PETG as the main material. A surface layer modifier prepared by reacting liquid cis-1,1-dimethylformamide, olefin-modified calcium carbonate / carbon black and hexafluorobutyl methacrylate is added to PETG to prepare a surface layer melt, an intermediate layer modifier prepared by reacting liquid cis-1,1-dimethylformamide, olefin-modified montmorillonite / carbon black is added to PETG to prepare an intermediate layer melt, an inner layer modifier prepared by reacting liquid cis-1,1-dimethylformamide, olefin-modified carbon black is added to PETG to prepare an inner layer melt, the surface layer melt, the intermediate layer melt and the inner layer melt are combined and extruded in a die head, and the obtained film is subjected to biaxial stretching to obtain a high light-shielding heat-shrinkable composite film, and the obtained heat-shrinkable composite film has high light-shielding and good barrier properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite film materials, and in particular to a high-light-shielding heat-shrinkable composite film and a preparation method thereof. Background Art

[0002] Heat shrinkable composite films are widely used to package various products, and have high requirements for light-shielding performance, puncture resistance and barrier performance. PETG (polyethylene terephthalate-1,4-cyclohexanedimethanol) has outstanding thermoforming performance, toughness and weather resistance, and its low heat deformation temperature. The preparation of heat shrinkable films can make up for the many defects of existing packaging products made of PVC and other materials in processing and use, and can achieve shrink packaging of beverage bottles, food, cosmetics, electronic products, etc. under low temperature conditions.

[0003] Chinese patent application CN112318990A discloses a high light-shielding PETG shrink film, including an inner layer, a core layer and an outer layer, wherein the inner layer is formed by copolymerization of colored PET waste bottles, 2,2-dimethyl-1,3-propylene glycol, titanium dioxide, carbon crystals, and red, yellow and blue dyes, the core layer is formed by copolymerization of colored PET waste bottles, 2,2-dimethyl-1,3-propylene glycol, titanium dioxide, and red, yellow and blue dyes, and the outer layer is formed by copolymerization of transparent PET waste bottles, 2,2-dimethyl-1,3-propylene glycol, and titanium dioxide, but titanium dioxide, carbon crystals, etc. cannot participate in the copolymerization reaction, and are physically mixed in the reaction system, so the light-shielding performance needs to be improved, and the PETG shrink film Although it has UV barrier properties, it has poor water barrier properties. Chinese patent application CN117962447A discloses a floatable white polyester heat shrinkable film, and the film layer structure is a three-layer structure of A / B / A. The raw materials of the A layer include PETG, LDPE and smooth polyester, and the raw materials of the B layer include NPG-modified PET, LDPE, white polyester and porogenic materials. The shading effect is improved by improving the whiteness of the film, but the light absorption capacity of white is insufficient, and the shading performance of the film needs to be improved. In addition, due to the addition of porogenic materials, the barrier performance of the film needs to be improved. In addition, the puncture resistance of the film also needs to be improved. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a high light-shielding heat-shrinkable composite film and a preparation method thereof, so as to solve the problem that the light-shielding performance, barrier performance and puncture resistance of the heat-shrinkable composite film in the prior art need to be improved.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a high light-shielding heat-shrinkable composite film comprises the following steps:

[0007] Step 1, preparing a surface layer melt, an intermediate layer melt and an inner layer melt;

[0008] Wherein, preparing the surface melt comprises the following steps:

[0009] S11, adding liquid butadiene rubber to toluene, stirring to obtain a butadiene rubber solution, adding olefin-modified calcium carbonate / carbon black and hexafluorobutyl methacrylate to the butadiene rubber solution, and continuing to stir to obtain a mixed solution;

[0010] Add the azobisisobutyronitrile solution dropwise to the mixed solution, react after the addition is complete, precipitate after the reaction is complete, filter, wash, and dry to obtain a surface modifier;

[0011] S12, melt-blending PETG, a surface modifier, an antioxidant, and a lubricant to obtain a surface melt;

[0012] The preparation of the intermediate layer melt comprises the following steps:

[0013] S21, adding liquid butadiene rubber to toluene, stirring to obtain a butadiene rubber solution, adding olefin-modified montmorillonite / carbon black to the butadiene rubber solution, and continuing to stir to obtain a mixed solution;

[0014] Add the azobisisobutyronitrile solution dropwise to the mixed solution, react after the addition is complete, precipitate after the reaction is complete, filter, wash, and dry to obtain an intermediate layer modifier;

[0015] S22, melt-blending PETG, an intermediate layer modifier, an antioxidant, and a lubricant to obtain an intermediate layer melt;

[0016] The preparation of the inner layer melt comprises the following steps:

[0017] S31, adding liquid butadiene rubber to toluene, stirring to obtain a butadiene rubber solution, adding olefin-modified carbon black to the butadiene rubber solution, and continuing to stir to obtain a mixed solution;

[0018] Add the azobisisobutyronitrile solution dropwise to the mixed solution, react after the addition is complete, precipitate after the reaction is complete, filter, wash, and dry to obtain an inner layer modifier;

[0019] S32, melt-blending PETG, an inner layer modifier, SBS (styrene-butadiene-styrene block copolymer), an antioxidant, and a lubricant to obtain an inner layer melt;

[0020] Step 2: extruding the surface layer melt, the middle layer melt and the inner layer melt together in a die head, and cooling them on a cooling roller to obtain a film;

[0021] The membrane comprises a surface membrane, an intermediate membrane and an inner membrane;

[0022] Step 3, biaxially stretching the film to obtain a heat-shrinkable composite film with high light-shielding properties;

[0023] The high light-shielding heat-shrinkable composite film comprises a surface film material, an intermediate film material and an inner film material.

[0024] Preferably, in step 1, when preparing the surface melt, in S11, the mass ratio of liquid butadiene rubber, toluene, olefin-modified calcium carbonate / carbon black, hexafluorobutyl methacrylate, and azobisisobutyronitrile solution is 200:(300-500):(30-40):(5-10):(10-15); the reaction conditions are to react at a temperature of 65-75°C for 6-8h under a nitrogen atmosphere.

[0025] Preferably, the olefin-modified calcium carbonate / carbon black is prepared by the following steps:

[0026] Calcium carbonate and carbon black are added to anhydrous ethanol, and after ultrasonic dispersion, γ-(methacryloyloxy)propyltrimethoxysilane is added to react. After the reaction is completed, the reaction is filtered, washed, and dried to obtain olefin-modified calcium carbonate / carbon black.

[0027] Preferably, the mass ratio of calcium carbonate, carbon black, anhydrous ethanol and γ-(methacryloyloxy)propyltrimethoxysilane is (5-10):(10-20):(150-200):(10-20), and the reaction conditions are 70-80° C. for 6-10 hours.

[0028] Preferably, in step 1, when preparing the surface melt, in S12, the mass ratio of PETG, surface modifier, antioxidant and lubricant is (75-80):(20-25):(0.5-1):(0.5-1), and the melting temperature is 200-220°C.

[0029] Preferably, in the step 1, when preparing the intermediate layer melt, in S21, the mass ratio of liquid butadiene rubber, toluene, olefin-modified montmorillonite / carbon black, and azobisisobutyronitrile solution is 200:(300-500):(30-40):(10-15); the reaction conditions are to react at a temperature of 65-75°C for 6-8h under a nitrogen atmosphere.

[0030] Preferably, the olefin-modified montmorillonite / carbon black is prepared by the following steps:

[0031] Montmorillonite and carbon black are added to anhydrous ethanol, and after ultrasonic dispersion, γ-(methacryloyloxy)propyltrimethoxysilane is added to react. After the reaction is completed, the reaction is filtered, washed, and dried to obtain olefin-modified montmorillonite / carbon black.

[0032] Preferably, the mass ratio of montmorillonite, carbon black, anhydrous ethanol and γ-(methacryloyloxy)propyltrimethoxysilane is (10-15):(15-20):(150-200):(15-25), and the reaction conditions are 70-80° C. for 6-10 hours.

[0033] Preferably, in step 1, when preparing the intermediate layer melt, in S22, the mass ratio of PETG, intermediate layer modifier, antioxidant and lubricant is (70-80):(20-30):(0.5-1):(0.5-1), and the melting temperature is 200-220°C.

[0034] Preferably, in the step 1, when preparing the inner layer melt, in S31, the mass ratio of liquid butadiene rubber, toluene, olefin-modified carbon black, and azobisisobutyronitrile solution is 200:(300-500):(20-30):(10-15); the reaction conditions are to react at a temperature of 65-75°C for 6-8h under a nitrogen atmosphere.

[0035] Preferably, the olefin-modified carbon black is prepared by the following steps:

[0036] The carbon black is added into anhydrous ethanol, and after ultrasonic dispersion, γ-(methacryloyloxy)propyltrimethoxysilane is added to react. After the reaction is completed, the reaction is filtered, washed, and dried to obtain olefin-modified carbon black.

[0037] Preferably, the mass ratio of carbon black, anhydrous ethanol and γ-(methacryloyloxy)propyltrimethoxysilane is (20-30):(150-200):(10-20), and the reaction conditions are 70-80° C. for 6-10 hours.

[0038] Preferably, in step 1, when preparing the intermediate layer melt, in S32, the mass ratio of PETG, inner layer modifier, SBS, antioxidant and lubricant is (70-80):(15-20):(5-10):(0.5-1):(0.5-1), and the melting temperature is 200-220°C.

[0039] Preferably, in step 1, the azobisisobutyronitrile solutions used in S11, S21 and S31 are the same;

[0040] The azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%.

[0041] Furthermore, the dropping time of the azobisisobutyronitrile solution is the same, which is 30-60 minutes.

[0042] Preferably, in step 1, the antioxidant and lubricant used in S12, S22, and S32 are the same;

[0043] The antioxidant includes pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the lubricant includes stearate.

[0044] Preferably, in step 2, the die temperature is 240-250° C., and the thickness of the membrane is 150-250 μm.

[0045] Preferably, the thickness ratio of the surface film, the middle film and the inner film is 3:4:3.

[0046] Preferably, in step 3, the biaxial stretching is performed by first performing longitudinal stretching and then performing transverse stretching;

[0047] The longitudinal stretching comprises preheating at 80-90°C, longitudinally stretching at 100-115°C at a ratio of 1.2-3 times to form a film, and after longitudinal stretching to form a film, setting at 80-90°C for 2-5s;

[0048] The transverse stretching comprises stretching the longitudinally stretched film after shaping at a temperature of 95-120° C. in the transverse direction at a ratio of 3-5.5 times, and shaping at a temperature of 70-95° C. after the transverse stretching, for a shaping time of 5-10 seconds.

[0049] The invention also discloses a high light-shielding heat-shrinkable composite film prepared by adopting the above-mentioned method for preparing a high light-shielding heat-shrinkable composite film.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] In the present invention, PETG is used as the main material to prepare the film material, and the PETG molecular chains are oriented and arranged in order in a direction parallel to the film plane through biaxial stretching, and the oriented PETG molecular chains are fixed through heat setting, which can promote PETG crystallization and improve the heat shrinkage performance of the PETG shrink film; a surface layer modifier is added to PETG to prepare a surface layer melt, an intermediate layer modifier is added to PETG to prepare an intermediate layer melt, and an inner layer modifier is added to PETG to prepare an inner layer melt. The surface layer melt, the intermediate layer melt and the inner layer melt are combined and extruded in a die head to obtain a film sheet, which is biaxially stretched to obtain a high light-shielding heat-shrinkable composite film. The obtained heat-shrinkable composite film has high light-shielding performance and good barrier performance and puncture resistance.

[0052] In the surface melt, the surface modifier added is prepared by the reaction of liquid butadiene rubber, olefin-modified calcium carbonate / carbon black and hexafluorobutyl methacrylate. The introduction of butadiene rubber and calcium carbonate can improve the toughness of the surface film material, thereby improving the puncture resistance of the surface film material. The introduction of carbon black can improve the light-shielding performance of the surface film material. The introduction of the fluorine-containing compound hexafluorobutyl methacrylate can improve the hydrophobicity of the surface film material, thereby improving the barrier performance of the surface film material. The olefin-modified calcium carbonate / carbon black and hexafluorobutyl methacrylate are grafted onto the butadiene rubber molecular chain under the action of an initiator. Through the mutual entanglement of the butadiene rubber molecular chain and the PETG molecular chain, the compatibility and dispersion uniformity of calcium carbonate and carbon black in PETG are good, the stability of hexafluorobutyl methacrylate in PETG is good, and the puncture resistance, light-shielding performance and barrier performance of the surface film material are high.

[0053] The middle layer modifier added to the middle layer melt is prepared by the reaction of liquid butadiene rubber and olefin-modified montmorillonite / carbon black. The introduction of butadiene rubber can improve the toughness of the middle layer film material, the introduction of montmorillonite can improve the barrier performance of the middle layer film material, and the introduction of carbon black can improve the light-shielding performance of the middle layer film material. The olefin-modified montmorillonite / carbon black is grafted onto the butadiene rubber molecular chain under the action of the initiator. Through the mutual entanglement of the butadiene rubber molecular chain and the PETG molecular chain, the compatibility and uniform dispersion of montmorillonite and carbon black in PETG are good, and the middle layer film material has high puncture resistance, high light-shielding performance and good barrier performance.

[0054] The inner layer modifier added to the inner layer melt is prepared by the reaction of liquid butadiene rubber and olefin-modified carbon black. The introduction of butadiene rubber can improve the toughness of the inner layer film material, and the introduction of carbon black can improve the light-shielding performance of the inner layer film material. The olefin-modified carbon black is grafted onto the butadiene rubber molecular chain under the action of the initiator. Through the mutual entanglement of the butadiene rubber molecular chain and the PETG molecular chain, the compatibility and dispersion uniformity of the carbon black in PETG are good, and the inner layer film material has high puncture resistance and light-shielding performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 The process flow chart of preparing a heat-shrinkable composite film with high light-shielding properties in the present invention;

[0056] Figure 2 A bar graph showing the test results of heat shrinkage properties of the high light-shielding heat-shrinkable composite films prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention;

[0057] Figure 3 A bar graph showing the light-shielding performance test results of the high light-shielding heat-shrinkable composite films prepared in Examples 1-5 of the present invention and Comparative Examples 1-2;

[0058] Figure 4It is a bar chart showing the barrier properties test results of the high light-shielding heat-shrinkable composite films prepared in Examples 1-5 of the present invention and Comparative Examples 1-2;

[0059] Figure 5 It is a bar graph showing the test results of the puncture resistance of the high light-shielding heat-shrinkable composite films prepared in Examples 1-5 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION

[0060] Example 1

[0061] A method for preparing a high light-shielding heat-shrinkable composite film comprises the following steps:

[0062] Step 1, preparing a surface layer melt, an intermediate layer melt and an inner layer melt;

[0063] Wherein, preparing the surface melt comprises the following steps:

[0064] S11, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified calcium carbonate / carbon black and hexafluorobutyl methacrylate to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0065] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 30 min. After the addition was completed, the mixture was reacted at 65° C. for 8 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain a surface modifier.

[0066] The mass ratio of liquid butadiene rubber, toluene, olefin-modified calcium carbonate / carbon black, hexafluorobutyl methacrylate, and azobisisobutyronitrile solution is 200:300:30:5:10; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0067] The alkenyl-modified calcium carbonate / carbon black is prepared by the following steps:

[0068] Calcium carbonate and carbon black are added to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40 kHz for 30 minutes, γ-(methacryloyloxy)propyltrimethoxysilane is added, and the mass ratio of calcium carbonate, carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 5:10:150:10, and the mixture is reacted at a temperature of 70°C for 10 hours. After the reaction is completed, the mixture is filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified calcium carbonate / carbon black;

[0069] S12, melt-blending PETG, a surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 80:20:0.5:0.5, and the melting temperature is 200° C., to obtain a surface melt;

[0070] The preparation of the intermediate layer melt comprises the following steps:

[0071] S21, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified montmorillonite / carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0072] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 30 min. After the addition was completed, the mixture was reacted at 65° C. for 8 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain an intermediate layer modifier.

[0073] The mass ratio of liquid butadiene rubber, toluene, olefin-modified montmorillonite / carbon black, and azobisisobutyronitrile solution is 200:300:30:10; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0074] The alkenyl-modified montmorillonite / carbon black is prepared by the following steps:

[0075] Add montmorillonite and carbon black to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40 kHz for 30 minutes, add γ-(methacryloyloxy)propyltrimethoxysilane, the mass ratio of montmorillonite, carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 10:15:150:15, react at 70°C for 10 hours, filter after the reaction, wash with ethanol 3 times, and dry in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified montmorillonite / carbon black;

[0076] S22, melt-blending PETG, an intermediate layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 80:20:0.5:0.5, and the melting temperature is 200° C., to obtain an intermediate layer melt;

[0077] The preparation of the inner layer melt comprises the following steps:

[0078] S31, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0079] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 30 min. After the addition was completed, the mixture was reacted at 65°C for 8 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50°C for 24 h to obtain an inner layer modifier.

[0080] The mass ratio of liquid butadiene rubber, toluene, olefin-modified carbon black and azobisisobutyronitrile solution is 200:300:20:10; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0081] The olefin-modified carbon black is prepared by the following steps:

[0082] Add carbon black to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40kHz for 30 minutes, add γ-(methacryloyloxy)propyltrimethoxysilane, the mass ratio of carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 20:150:10, react at 70°C for 10 hours, filter after the reaction, wash with ethanol 3 times, and dry in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified carbon black;

[0083] S32, melt-blending PETG, an inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 80:15:5:0.5:0.5, and the melting temperature is 200° C., to obtain an intermediate layer melt;

[0084] Step 2: Extruding the surface layer melt, the middle layer melt and the inner layer melt together in a die head at a die head temperature of 240° C. and cooling on a cooling roller to obtain a film having a thickness of 200 μm;

[0085] The membrane comprises a surface membrane, an intermediate membrane and an inner membrane;

[0086] The thickness ratio of the surface membrane, the middle membrane and the inner membrane is 3:4:3;

[0087] Step 3, biaxially stretching the film to obtain a heat-shrinkable composite film with high light-shielding properties;

[0088] Among them, biaxial stretching is first longitudinal stretching and then transverse stretching;

[0089] The longitudinal stretching is preheated at 85°C, longitudinally stretched at 110°C at a ratio of 3 times to form a film, and after longitudinal stretching to form a film, fixed at 85°C for 4s;

[0090] The transverse stretching includes stretching the longitudinally stretched film after shaping at a temperature of 110° C. at a ratio of 4.5 in the transverse direction, and shaping at a temperature of 85° C. after the transverse stretching, with a shaping time of 8 seconds.

[0091] Example 2

[0092] A method for preparing a high light-shielding heat-shrinkable composite film comprises the following steps:

[0093] Step 1, preparing a surface layer melt, an intermediate layer melt and an inner layer melt;

[0094] Wherein, preparing the surface melt comprises the following steps:

[0095] S11, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified calcium carbonate / carbon black and hexafluorobutyl methacrylate to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0096] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 60 min. After the addition was completed, the mixture was reacted at 75° C. under a nitrogen atmosphere for 6 h. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain a surface modifier.

[0097] The mass ratio of liquid butadiene rubber, toluene, olefin-modified calcium carbonate / carbon black, hexafluorobutyl methacrylate, and azobisisobutyronitrile solution is 200:500:40:10:15; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0098] The alkenyl-modified calcium carbonate / carbon black is prepared by the following steps:

[0099] Calcium carbonate and carbon black are added to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40 kHz for 30 minutes, γ-(methacryloyloxy)propyltrimethoxysilane is added, and the mass ratio of calcium carbonate, carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 10:20:200:20, and the mixture is reacted at 80° C. for 6 hours. After the reaction is completed, the mixture is filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50° C. for 24 hours to obtain olefin-modified calcium carbonate / carbon black;

[0100] S12, melt-blending PETG, a surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 75:25:1:1, and the melting temperature is 220° C., to obtain a surface melt;

[0101] The preparation of the intermediate layer melt comprises the following steps:

[0102] S21, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified montmorillonite / carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0103] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 60 min. After the addition was completed, the mixture was reacted at 65° C. for 8 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain an intermediate layer modifier.

[0104] The mass ratio of liquid butadiene rubber, toluene, olefin-modified montmorillonite / carbon black, and azobisisobutyronitrile solution is 200:500:40:15; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0105] The alkenyl-modified montmorillonite / carbon black is prepared by the following steps:

[0106] Montmorillonite and carbon black are added to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40 kHz for 30 minutes, γ-(methacryloyloxy)propyltrimethoxysilane is added, and the mass ratio of montmorillonite, carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 15:20:200:25. The mixture is reacted at 80° C. for 6 hours. After the reaction is completed, the mixture is filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50° C. for 24 hours to obtain olefin-modified montmorillonite / carbon black;

[0107] S22, melt-blending PETG, an intermediate layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 70:30:1:1, and the melting temperature is 220° C., to obtain an intermediate layer melt;

[0108] The preparation of the inner layer melt comprises the following steps:

[0109] S31, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0110] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 60 min. After the addition was completed, the mixture was reacted at 75°C for 6 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50°C for 24 h to obtain an inner layer modifier.

[0111] The mass ratio of liquid butadiene rubber, toluene, olefin-modified carbon black and azobisisobutyronitrile solution is 200:500:30:15; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0112] The olefin-modified carbon black is prepared by the following steps:

[0113] Add carbon black to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40kHz for 30 minutes, add γ-(methacryloyloxy)propyltrimethoxysilane, the mass ratio of carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 30:200:20, react at 80°C for 6 hours, filter after the reaction, wash with ethanol 3 times, and dry in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified carbon black;

[0114] S32, melt-blending PETG, an inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 70:20:10:1:1, and the melting temperature is 220° C., to obtain an intermediate layer melt;

[0115] Step 2: Extruding the surface layer melt, the middle layer melt and the inner layer melt together in a die head at a die head temperature of 250° C. and cooling on a cooling roller to obtain a film having a thickness of 200 μm;

[0116] The membrane comprises a surface membrane, an intermediate membrane and an inner membrane;

[0117] The thickness ratio of the surface membrane, the middle membrane and the inner membrane is 3:4:3;

[0118] Step 3, biaxially stretching the film to obtain a heat-shrinkable composite film with high light-shielding properties;

[0119] Among them, biaxial stretching is first longitudinal stretching and then transverse stretching;

[0120] The longitudinal stretching is preheated at 85°C, longitudinally stretched at 110°C at a ratio of 3 times to form a film, and after longitudinal stretching to form a film, fixed at 85°C for 4s;

[0121] The transverse stretching includes stretching the longitudinally stretched film after shaping at a temperature of 110° C. at a ratio of 4.5 in the transverse direction, and shaping at a temperature of 85° C. after the transverse stretching, with a shaping time of 8 seconds.

[0122] Example 3

[0123] A method for preparing a high light-shielding heat-shrinkable composite film comprises the following steps:

[0124] Step 1, preparing a surface layer melt, an intermediate layer melt and an inner layer melt;

[0125] Wherein, preparing the surface melt comprises the following steps:

[0126] S11, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified calcium carbonate / carbon black and hexafluorobutyl methacrylate to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0127] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 60 min. After the addition was completed, the mixture was reacted at 70°C for 7 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50°C for 24 h to obtain a surface modifier.

[0128] The mass ratio of liquid butadiene rubber, toluene, olefin-modified calcium carbonate / carbon black, hexafluorobutyl methacrylate, and azobisisobutyronitrile solution is 200:350:33:6:11; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0129] The alkenyl-modified calcium carbonate / carbon black is prepared by the following steps:

[0130] Calcium carbonate and carbon black are added to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40 kHz for 30 minutes, γ-(methacryloyloxy)propyltrimethoxysilane is added, and the mass ratio of calcium carbonate, carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 6:12:160:13. The mixture is reacted at 75°C for 8 hours. After the reaction is completed, the mixture is filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified calcium carbonate / carbon black;

[0131] S12, melt-blending PETG, a surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 76:24:0.6:0.6, and the melting temperature is 210° C., to obtain a surface melt;

[0132] The preparation of the intermediate layer melt comprises the following steps:

[0133] S21, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified montmorillonite / carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0134] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 45 min. After the addition was completed, the mixture was reacted at 70° C. under a nitrogen atmosphere for 7 h. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain an intermediate layer modifier.

[0135] The mass ratio of liquid butadiene rubber, toluene, olefin-modified montmorillonite / carbon black, and azobisisobutyronitrile solution is 200:350:32:11; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0136] The alkenyl-modified montmorillonite / carbon black is prepared by the following steps:

[0137] Add montmorillonite and carbon black to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40 kHz for 30 minutes, add γ-(methacryloyloxy)propyltrimethoxysilane, the mass ratio of montmorillonite, carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 11:16:160:18, react at 75°C for 8 hours, filter after the reaction, wash with ethanol 3 times, and dry in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified montmorillonite / carbon black;

[0138] S22, melt-blending PETG, an intermediate layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 72:28:0.6:0.6, and the melting temperature is 210° C., to obtain an intermediate layer melt;

[0139] The preparation of the inner layer melt comprises the following steps:

[0140] S31, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0141] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 45 min. After the addition was completed, the mixture was reacted at 70°C for 7 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50°C for 24 h to obtain an inner layer modifier.

[0142] The mass ratio of liquid butadiene rubber, toluene, olefin-modified carbon black and azobisisobutyronitrile solution is 200:350:22:11; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0143] The olefin-modified carbon black is prepared by the following steps:

[0144] Add carbon black to anhydrous ethanol, ultrasonically disperse at a frequency of 40kHz for 30 minutes, add γ-(methacryloyloxy)propyltrimethoxysilane, the mass ratio of carbon black, anhydrous ethanol and γ-(methacryloyloxy)propyltrimethoxysilane is 22:160:13, react at 75°C for 8 hours, filter after the reaction, wash with ethanol 3 times, and dry in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified carbon black;

[0145] S32, melt-blending PETG, an inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 72:19:9:0.6:0.6, and the melting temperature is 210° C., to obtain an intermediate layer melt;

[0146] Step 2: Extruding the surface layer melt, the middle layer melt and the inner layer melt together in a die head at a die head temperature of 245° C. and cooling on a cooling roller to obtain a film having a thickness of 200 μm;

[0147] The membrane comprises a surface membrane, an intermediate membrane and an inner membrane;

[0148] The thickness ratio of the surface membrane, the middle membrane and the inner membrane is 3:4:3;

[0149] Step 3, biaxially stretching the film to obtain a heat-shrinkable composite film with high light-shielding properties;

[0150] Among them, biaxial stretching is first longitudinal stretching and then transverse stretching;

[0151] The longitudinal stretching is preheated at 85°C, longitudinally stretched at 110°C at a ratio of 3 times to form a film, and after longitudinal stretching to form a film, fixed at 85°C for 4s;

[0152] The transverse stretching includes stretching the longitudinally stretched film after shaping at a temperature of 110° C. at a ratio of 4.5 in the transverse direction, and shaping at a temperature of 85° C. after the transverse stretching, with a shaping time of 8 seconds.

[0153] Example 4

[0154] A method for preparing a high light-shielding heat-shrinkable composite film comprises the following steps:

[0155] Step 1, preparing a surface layer melt, an intermediate layer melt and an inner layer melt;

[0156] Wherein, preparing the surface melt comprises the following steps:

[0157] S11, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified calcium carbonate / carbon black and hexafluorobutyl methacrylate to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0158] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 45 min. After the addition was completed, the mixture was reacted at 70° C. under a nitrogen atmosphere for 7 h. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain a surface modifier.

[0159] The mass ratio of liquid butadiene rubber, toluene, olefin-modified calcium carbonate / carbon black, hexafluorobutyl methacrylate, and azobisisobutyronitrile solution is 200:400:35:7.5:12.5; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0160] The alkenyl-modified calcium carbonate / carbon black is prepared by the following steps:

[0161] Calcium carbonate and carbon black are added to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40 kHz for 30 minutes, γ-(methacryloyloxy)propyltrimethoxysilane is added, and the mass ratio of calcium carbonate, carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 7.5:15:175:15. The mixture is reacted at 75°C for 8 hours. After the reaction is completed, the mixture is filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified calcium carbonate / carbon black;

[0162] S12, melt-blending PETG, a surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 78:22:0.8:0.8, and the melting temperature is 210° C., to obtain a surface melt;

[0163] The preparation of the intermediate layer melt comprises the following steps:

[0164] S21, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified montmorillonite / carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0165] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 45 min. After the addition was completed, the mixture was reacted at 70° C. under a nitrogen atmosphere for 7 h. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain an intermediate layer modifier.

[0166] The mass ratio of liquid butadiene rubber, toluene, olefin-modified montmorillonite / carbon black, and azobisisobutyronitrile solution is 200:400:35:12.5; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0167] The alkenyl-modified montmorillonite / carbon black is prepared by the following steps:

[0168] Add montmorillonite and carbon black to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40 kHz for 30 minutes, add γ-(methacryloyloxy)propyltrimethoxysilane, the mass ratio of montmorillonite, carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 12.5:17.5:175:20, react at 75°C for 8 hours, filter after the reaction, wash with ethanol 3 times, and dry in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified montmorillonite / carbon black;

[0169] S22, melt-blending PETG, an intermediate layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 75:25:0.75:0.75, and the melting temperature is 210° C., to obtain an intermediate layer melt;

[0170] The preparation of the inner layer melt comprises the following steps:

[0171] S31, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0172] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 45 min. After the addition was completed, the mixture was reacted at 70°C for 7 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50°C for 24 h to obtain an inner layer modifier.

[0173] The mass ratio of liquid butadiene rubber, toluene, olefin-modified carbon black and azobisisobutyronitrile solution is 200:400:25:12.5; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0174] The olefin-modified carbon black is prepared by the following steps:

[0175] Add carbon black to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40kHz for 30 minutes, add γ-(methacryloyloxy)propyltrimethoxysilane, the mass ratio of carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 25:175:15, react at 75°C for 8 hours, filter after the reaction, wash with ethanol 3 times, and dry in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified carbon black;

[0176] S32, melt-blending PETG, an inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 75:18:7:0.75:0.75, and the melting temperature is 210° C., to obtain an intermediate layer melt;

[0177] Step 2: Extruding the surface layer melt, the middle layer melt and the inner layer melt together in a die head at a die head temperature of 245° C. and cooling on a cooling roller to obtain a film having a thickness of 200 μm;

[0178] The membrane comprises a surface membrane, an intermediate membrane and an inner membrane;

[0179] The thickness ratio of the surface membrane, the middle membrane and the inner membrane is 3:4:3;

[0180] Step 3, biaxially stretching the film to obtain a heat-shrinkable composite film with high light-shielding properties;

[0181] Among them, biaxial stretching is first longitudinal stretching and then transverse stretching;

[0182] The longitudinal stretching is preheated at 85°C, longitudinally stretched at 110°C at a ratio of 3 times to form a film, and after longitudinal stretching to form a film, fixed at 85°C for 4s;

[0183] The transverse stretching includes stretching the longitudinally stretched film after shaping at a temperature of 110° C. at a ratio of 4.5 in the transverse direction, and shaping at a temperature of 85° C. after the transverse stretching, with a shaping time of 8 seconds.

[0184] Example 5

[0185] A method for preparing a high light-shielding heat-shrinkable composite film comprises the following steps:

[0186] Step 1, preparing a surface layer melt, an intermediate layer melt and an inner layer melt;

[0187] Wherein, preparing the surface melt comprises the following steps:

[0188] S11, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified calcium carbonate / carbon black and hexafluorobutyl methacrylate to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0189] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 45 min. After the addition was completed, the mixture was reacted at 70° C. under a nitrogen atmosphere for 7 h. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain a surface modifier.

[0190] The mass ratio of liquid butadiene rubber, toluene, olefin-modified calcium carbonate / carbon black, hexafluorobutyl methacrylate, and azobisisobutyronitrile solution is 200:450:38:9:14; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0191] The alkenyl-modified calcium carbonate / carbon black is prepared by the following steps:

[0192] Calcium carbonate and carbon black are added to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40 kHz for 30 minutes, γ-(methacryloyloxy)propyltrimethoxysilane is added, and the mass ratio of calcium carbonate, carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 9:18:190:18, and the mixture is reacted at 75°C for 8 hours. After the reaction is completed, the mixture is filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified calcium carbonate / carbon black;

[0193] S12, melt-blending PETG, a surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 79:21:0.9:0.9, and the melting temperature is 210° C., to obtain a surface melt;

[0194] The preparation of the intermediate layer melt comprises the following steps:

[0195] S21, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified montmorillonite / carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0196] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 45 min. After the addition was completed, the mixture was reacted at 70° C. under a nitrogen atmosphere for 7 h. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain an intermediate layer modifier.

[0197] The mass ratio of liquid butadiene rubber, toluene, olefin-modified montmorillonite / carbon black, and azobisisobutyronitrile solution is 200:450:38:14; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0198] The alkenyl-modified montmorillonite / carbon black is prepared by the following steps:

[0199] Montmorillonite and carbon black are added to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40 kHz for 30 minutes, γ-(methacryloyloxy)propyltrimethoxysilane is added, and the mass ratio of montmorillonite, carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 14:19:190:23, and the mixture is reacted at 75°C for 8 hours. After the reaction is completed, the mixture is filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified montmorillonite / carbon black;

[0200] S22, melt-blending PETG, an intermediate layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 78:22:0.9:0.9, and the melting temperature is 210° C., to obtain an intermediate layer melt;

[0201] The preparation of the inner layer melt comprises the following steps:

[0202] S31, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0203] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 45 min. After the addition was completed, the mixture was reacted at 70°C for 7 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50°C for 24 h to obtain an inner layer modifier.

[0204] The mass ratio of liquid butadiene rubber, toluene, olefin-modified carbon black and azobisisobutyronitrile solution is 200:450:28:14; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0205] The olefin-modified carbon black is prepared by the following steps:

[0206] Add carbon black to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40kHz for 30 minutes, add γ-(methacryloyloxy)propyltrimethoxysilane, the mass ratio of carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 28:190:18, react at 75°C for 8 hours, filter after the reaction, wash with ethanol 3 times, and dry in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified carbon black;

[0207] S32, melt-blending PETG, an inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 78:16:6:0.8:0.8, and the melting temperature is 210° C., to obtain an intermediate layer melt;

[0208] Step 2: Extruding the surface layer melt, the middle layer melt and the inner layer melt together in a die head at a die head temperature of 245° C. and cooling on a cooling roller to obtain a film having a thickness of 200 μm;

[0209] The membrane comprises a surface membrane, an intermediate membrane and an inner membrane;

[0210] The thickness ratio of the surface membrane, the middle membrane and the inner membrane is 3:4:3;

[0211] Step 3, biaxially stretching the film to obtain a heat-shrinkable composite film with high light-shielding properties;

[0212] Among them, biaxial stretching is first longitudinal stretching and then transverse stretching;

[0213] The longitudinal stretching is preheated at 85°C, longitudinally stretched at 110°C at a ratio of 3 times to form a film, and after longitudinal stretching to form a film, fixed at 85°C for 4s;

[0214] The transverse stretching includes stretching the longitudinally stretched film after shaping at a temperature of 110° C. at a ratio of 4.5 in the transverse direction, and shaping at a temperature of 85° C. after the transverse stretching, with a shaping time of 8 seconds.

[0215] Comparative Example 1

[0216] A method for preparing a high light-shielding heat-shrinkable composite film comprises the following steps:

[0217] Step 1, preparing a surface layer melt, an intermediate layer melt and an inner layer melt;

[0218] Wherein, preparing the surface melt comprises the following steps:

[0219] S11, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified calcium carbonate / carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0220] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 30 min. After the addition was completed, the mixture was reacted at 65° C. for 8 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain a surface modifier.

[0221] The mass ratio of liquid butadiene rubber, toluene, olefin-modified calcium carbonate / carbon black, and azobisisobutyronitrile solution is 200:300:30:10; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0222] The alkenyl-modified calcium carbonate / carbon black is prepared by the following steps:

[0223] Calcium carbonate and carbon black are added to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40 kHz for 30 minutes, γ-(methacryloyloxy)propyltrimethoxysilane is added, and the mass ratio of calcium carbonate, carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 5:10:150:10, and the mixture is reacted at a temperature of 70°C for 10 hours. After the reaction is completed, the mixture is filtered, washed with ethanol for 3 times, and dried in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified calcium carbonate / carbon black;

[0224] S12, melt-blending PETG, a surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 80:19.7:0.5:0.5, and the melting temperature is 200° C., to obtain a surface melt;

[0225] The preparation of the intermediate layer melt comprises the following steps:

[0226] S21, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0227] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 30 min. After the addition was completed, the mixture was reacted at 65° C. for 8 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50° C. for 24 h to obtain an intermediate layer modifier.

[0228] The mass ratio of liquid butadiene rubber, toluene, olefin-modified carbon black and azobisisobutyronitrile solution is 200:300:18:10; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0229] The olefin-modified carbon black is prepared by the following steps:

[0230] Add carbon black to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40kHz for 30 minutes, add γ-(methacryloyloxy)propyltrimethoxysilane, the mass ratio of carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 15:150:9, react at 70°C for 10 hours, filter after the reaction, wash with ethanol 3 times, and dry in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified carbon black;

[0231] S22, melt-blending PETG, an intermediate layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the surface layer modifier, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 80:19:0.5:0.5, and the melting temperature is 200° C., to obtain an intermediate layer melt;

[0232] The preparation of the inner layer melt comprises the following steps:

[0233] S31, adding liquid butadiene rubber to toluene, stirring and mixing at a stirring speed of 300 r / min for 30 min to obtain a butadiene rubber solution, adding olefin-modified carbon black to the butadiene rubber solution, and continuing to stir and mix at a stirring speed of 300 r / min for 60 min to obtain a mixed solution;

[0234] Azobisisobutyronitrile solution was added dropwise to the mixed solution for 30 min. After the addition was completed, the mixture was reacted at 65°C for 8 h under a nitrogen atmosphere. After the reaction was completed, petroleum ether twice the mass of toluene was added for precipitation, and the mixture was filtered. The filtered precipitate was washed with methanol for 3 times and dried in a vacuum drying oven at 50°C for 24 h to obtain an inner layer modifier.

[0235] The mass ratio of liquid butadiene rubber, toluene, olefin-modified carbon black and azobisisobutyronitrile solution is 200:300:20:10; the azobisisobutyronitrile solution is prepared from azobisisobutyronitrile and toluene, and the mass percentage of azobisisobutyronitrile in the azobisisobutyronitrile solution is 0.5%;

[0236] The olefin-modified carbon black is prepared by the following steps:

[0237] Add carbon black to anhydrous ethanol, and after ultrasonic dispersion at a frequency of 40kHz for 30 minutes, add γ-(methacryloyloxy)propyltrimethoxysilane, the mass ratio of carbon black, anhydrous ethanol, and γ-(methacryloyloxy)propyltrimethoxysilane is 20:150:10, react at 70°C for 10 hours, filter after the reaction, wash with ethanol 3 times, and dry in a vacuum drying oven at 50°C for 24 hours to obtain olefin-modified carbon black;

[0238] S32, melt-blending PETG, an inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate, wherein the mass ratio of PETG, the inner layer modifier, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and calcium stearate is 80:15:5:0.5:0.5, and the melting temperature is 200° C., to obtain an intermediate layer melt;

[0239] Step 2: Extruding the surface layer melt, the middle layer melt and the inner layer melt together in a die head at a die head temperature of 240° C. and cooling on a cooling roller to obtain a film having a thickness of 200 μm;

[0240] The membrane comprises a surface membrane, an intermediate membrane and an inner membrane;

[0241] The thickness ratio of the surface membrane, the middle membrane and the inner membrane is 3:4:3;

[0242] Step 3, biaxially stretching the film to obtain a heat-shrinkable composite film with high light-shielding properties;

[0243] Among them, biaxial stretching is first longitudinal stretching and then transverse stretching;

[0244] The longitudinal stretching is preheated at 85°C, longitudinally stretched at 110°C at a ratio of 3 times to form a film, and after longitudinal stretching to form a film, fixed at 85°C for 4s;

[0245] The transverse stretching includes stretching the longitudinally stretched film after shaping at a temperature of 110° C. at a ratio of 4.5 in the transverse direction, and shaping at a temperature of 85° C. after the transverse stretching, with a shaping time of 8 seconds.

[0246] Comparative Example 2

[0247] A method for preparing a high light-shielding heat-shrinkable composite film comprises the following steps:

[0248] Step 1, preparing a surface layer melt, an intermediate layer melt and an inner layer melt;

[0249] Wherein, preparing the surface melt comprises the following steps:

[0250] PETG, liquid butadiene rubber, carbon black, calcium carbonate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and calcium stearate are melt-blended, wherein the mass ratio of PETG, liquid butadiene rubber, carbon black, calcium carbonate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and calcium stearate is 80:17.3:1.6:0.8:0.5:0.5, and the melting temperature is 200° C. to obtain a surface melt;

[0251] The preparation of the intermediate layer melt comprises the following steps:

[0252] PETG, liquid butadiene rubber, carbon black, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and calcium stearate are melt-blended, wherein the mass ratio of PETG, liquid butadiene rubber, carbon black, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and calcium stearate is 80:17.6:1.4:0.5:0.5, and the melting temperature is 200° C., to obtain an intermediate layer melt;

[0253] The preparation of the inner layer melt comprises the following steps:

[0254] PETG, liquid butadiene rubber, carbon black, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and calcium stearate are melt-blended, wherein the mass ratio of PETG, liquid butadiene rubber, carbon black, SBS, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and calcium stearate is 80:13.8:1.7:5:0.5:0.5, and the melting temperature is 200° C. to obtain an intermediate layer melt;

[0255] Step 2: Extruding the surface layer melt, the middle layer melt and the inner layer melt together in a die head at a die head temperature of 240° C. and cooling on a cooling roller to obtain a film having a thickness of 200 μm;

[0256] The membrane comprises a surface membrane, an intermediate membrane and an inner membrane;

[0257] The thickness ratio of the surface membrane, the middle membrane and the inner membrane is 3:4:3;

[0258] Step 3, biaxially stretching the film to obtain a heat-shrinkable composite film with high light-shielding properties;

[0259] Among them, biaxial stretching is first longitudinal stretching and then transverse stretching;

[0260] The longitudinal stretching is preheated at 85°C, longitudinally stretched at 110°C at a ratio of 3 times to form a film, and after longitudinal stretching to form a film, fixed at 85°C for 4s;

[0261] The transverse stretching includes stretching the longitudinally stretched film after shaping at a temperature of 110° C. at a ratio of 4.5 in the transverse direction, and shaping at a temperature of 85° C. after the transverse stretching, with a shaping time of 8 seconds.

[0262] In the above embodiments and comparative examples:

[0263] Liquid butadiene rubber was purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd., molecular weight: 10000; calcium carbonate was purchased from Guangzhou Yifeng Chemical Technology Co., Ltd., model: TY-168, particle size: 50nm; carbon black was purchased from Shandong Wanhua Tianhe New Materials Co., Ltd., model: carbon black N330, 500μm sieve residue mg / kg≤10; PETG was purchased from Suzhou Jiangcangfa Plastic Chemical Co., Ltd., manufacturer: South Korea SK, item number: K2012, density: 1.27g / cm 3 , heat deformation temperature: 70℃; calcium stearate was purchased from Suzhou Liansheng Chemical Co., Ltd., CAS No.: 1592-23-0; montmorillonite was purchased from Shanghai Wanzhao Fine Chemical Co., Ltd., model: WSG-PN06, mesh number: 400 mesh; SBS was purchased from Shanghai Sanlian Industrial Co., Ltd., origin: Baling Petrochemical, brand: YH-792, S / B ratio: 40 / 60.

[0264] Test example

[0265] The performance tests were performed on the high light-shielding heat-shrinkable composite films prepared in Examples 1-5 and Comparative Examples 1-2:

[0266] (1) Thermal shrinkage performance test: The composite films prepared in Examples 1-5 and Comparative Examples 1-2 were cut into 5 specimens of 100 mm × 100 mm (± 0.1 mm), and a marking line was drawn on the specimens in the longitudinal and transverse directions, and the longitudinal and transverse directions were marked. The specimens were placed flat and quickly immersed in a constant temperature medium of 100°C ± 2°C. After 10 seconds, they were taken out and immersed in a spare normal temperature water bath. After the specimens were cooled, they were taken out and placed horizontally. The longitudinal and transverse lengths were measured along the marking lines, and the thermal shrinkage rate of the specimens was calculated. The arithmetic mean was taken as the measurement result, accurate to one decimal place.

[0267] The thermal shrinkage calculation formula is as follows:

[0268] S = (L0-L) / L0×100;

[0269] Where: S-heat shrinkage, %; L0-length of the sample marking line before heating, mm; L-length of the sample marking line after heating, mm; the calculation results of longitudinal heat shrinkage (MD) and transverse heat shrinkage (TD) are shown in Table 1:

[0270] Table 1

[0271] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 TD(%) 58 57 58 59 57 57 58 MD(%) 24 25 24 23 25 23 24

[0272] As shown in Table 1, the composite film prepared by the present invention has a high heat shrinkage rate and good heat shrinkage performance. Through biaxial stretching, the PETG molecular chains are oriented and arranged in an orderly manner in a direction parallel to the film plane, and the oriented PETG molecular chains are fixed by heat setting, which can promote PETG crystallization and improve the heat shrinkage performance of the PETG shrink film.

[0273] (2) Light-shielding performance test: The light transmittance of the composite films prepared in Examples 1-5 and Comparative Examples 1-2 was measured with reference to the standard GB / T2410-2008 "Determination of light transmittance and haze of transparent plastics". The results are shown in Table 2:

[0274] Table 2

[0275]

[0276] As can be seen from Table 2, the composite film prepared by the present invention has low light transmittance and good light-shielding performance. When preparing the surface layer melt, the middle layer melt and the inner layer melt, carbon black is added to the surface layer modifier, the middle layer modifier and the inner layer modifier respectively. The introduction of carbon black can improve the light-shielding performance of the film material. After the carbon black is modified by olefin groups, it is grafted onto the cis-butyl rubber molecular chain under the action of an initiator. Through the mutual entanglement of the butyl rubber molecular chain and the PETG molecular chain, the carbon black has good compatibility and uniform dispersion in PETG, and the composite film material has high light-shielding performance. Compared with Example 1, in Comparative Example 1, when preparing the surface layer melt, the added surface layer modifier does not contain hexafluorobutyl methacrylate, and when preparing the middle layer melt, the added middle layer modifier does not contain montmorillonite, which will not have a significant impact on the light-shielding performance of the composite film material; compared with Comparative Example 1, in Comparative Example 2, when preparing the surface layer melt, the middle layer melt and the inner layer melt, the carbon black is not chemically bonded to the butadiene rubber molecular chain, the compatibility and dispersion uniformity in PETG are reduced, and the light-shielding performance is reduced.

[0277] (3) Barrier performance test: The water vapor permeability of the composite films prepared in Examples 1-5 and Comparative Examples 1-2 was measured. The measurement method was based on the standard GB / T1037-2021 "Determination of water vapor permeability of plastic films and sheets by cup weight gain or weight loss method". The test temperature was (38±0.6)°C and the relative humidity was 90%±2%. During the test, the surface layer of the composite film (i.e., the side containing the surface modifier) ​​was facing the high pressure side. The measurement results are shown in Table 3:

[0278] Table 3

[0279]

[0280] As shown in Table 3, the composite film prepared by the present invention has low water vapor permeability and good barrier properties. When preparing the surface layer melt, the introduction of the fluorine-containing compound hexafluorobutyl methacrylate in the surface layer modifier can improve the hydrophobicity of the surface layer film material, and the hexafluorobutyl methacrylate is grafted onto the cis-1,4-butadiene rubber molecular chain under the action of the initiator, and has good stability in PETG, which can improve the barrier properties of the surface layer film material to water. When preparing the middle layer melt, the introduction of montmorillonite can improve the barrier properties of the middle layer film material. After montmorillonite is modified by olefin groups, it is grafted onto the cis-1,4-butadiene rubber molecular chain under the action of the initiator. Through the mutual entanglement of the 1,4-butadiene rubber molecular chain and the PETG molecular chain, the compatibility and dispersion uniformity of montmorillonite in PETG are good, and the barrier properties of the middle layer film material are good. Compared with Example 1, in Comparative Examples 1 and 2, when preparing the surface layer melt, the surface layer modifier added did not contain hexafluorobutyl methacrylate, and when preparing the intermediate layer melt, the intermediate layer modifier added did not contain montmorillonite, and the barrier properties of the composite film material were reduced.

[0281] (4) Puncture resistance test: The puncture strength of the composite films prepared in Examples 1-5 and Comparative Examples 1-2 was measured. The measurement method was based on 6.6.13 of GB / T10004-2008 "Plastic composite films for packaging, dry composite bags, and extrusion composites". Five samples with a diameter of 100 mm were mounted on the sample film fixing clamp ring. Then, a steel needle with a diameter of 1.0 mm and a spherical top radius of 0.5 mm was used to remove the puncture at a speed of (50±5) mm / min. The maximum load of the steel needle penetrating the sample was read, and the arithmetic mean was taken as the measurement result. The measurement results are shown in Table 4:

[0282] Table 4

[0283]

[0284] As can be seen from Table 4, the composite film prepared by the present invention has high puncture force and good puncture resistance. When preparing the surface melt, the introduction of cis-1,4-butadiene rubber and calcium carbonate in the surface modifier can improve the toughness of the surface film material, thereby improving the puncture resistance of the surface film material, and calcium carbonate is grafted onto the cis-1,4-butadiene rubber molecular chain under the action of the initiator. Through the mutual entanglement of the cis-1,4-butadiene rubber molecular chain and the PETG molecular chain, the compatibility and dispersion uniformity of calcium carbonate in PETG are good, which can further improve the puncture resistance of the surface film material. When preparing the middle layer melt and the inner layer melt, the introduction of cis-1,4-butadiene rubber can improve the toughness of the middle layer film material and the inner layer film material, thereby improving the puncture resistance of the middle layer film material and the inner layer film material. Compared with Example 1, in Comparative Examples 1 and 2, when preparing the surface melt, calcium carbonate is not connected to the cis-1,4-butadiene rubber molecular chain by chemical bonding, and its compatibility and dispersion uniformity in PETG are reduced, and the puncture resistance is reduced.

[0285] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high light-shielding heat-shrinkable composite film, characterized in that: The following steps are involved: Step 1, preparing a surface layer melt, an intermediate layer melt and an inner layer melt; Wherein, preparing the surface melt comprises the following steps: S11, adding liquid butadiene rubber to toluene, stirring to obtain a butadiene rubber solution, adding olefin-modified calcium carbonate / carbon black and hexafluorobutyl methacrylate to the butadiene rubber solution, and continuing to stir to obtain a mixed solution; Add the azobisisobutyronitrile solution dropwise to the mixed solution, react after the addition is complete, precipitate after the reaction is complete, filter, wash, and dry to obtain a surface modifier; The mass ratio of liquid butadiene rubber, toluene, olefin-modified calcium carbonate / carbon black, hexafluorobutyl methacrylate, and azobisisobutyronitrile solution is 200:(300-500):(30-40):(5-10):(10-15); the reaction conditions are to react at a temperature of 65-75° C. for 6-8 hours under a nitrogen atmosphere; S12, melt-blending PETG, a surface modifier, an antioxidant, and a lubricant to obtain a surface melt; Wherein, the mass ratio of PETG, surface modifier, antioxidant and lubricant is (75-80):(20-25):(0.5-1):(0.5-1), and the melting temperature is 200-220°C; The preparation of the intermediate layer melt comprises the following steps: S21, adding liquid butadiene rubber to toluene, stirring to obtain a butadiene rubber solution, adding olefin-modified montmorillonite / carbon black to the butadiene rubber solution, and continuing to stir to obtain a mixed solution; Add the azobisisobutyronitrile solution dropwise to the mixed solution, react after the addition is complete, precipitate after the reaction is complete, filter, wash, and dry to obtain an intermediate layer modifier; The mass ratio of liquid butadiene rubber, toluene, olefin-modified montmorillonite / carbon black, and azobisisobutyronitrile solution is 200:(300-500):(30-40):(10-15); the reaction conditions are to react at a temperature of 65-75° C. for 6-8 hours under a nitrogen atmosphere; S22, melt-blending PETG, an intermediate layer modifier, an antioxidant, and a lubricant to obtain an intermediate layer melt; Wherein, the mass ratio of PETG, intermediate layer modifier, antioxidant and lubricant is (70-80):(20-30):(0.5-1):(0.5-1), and the melting temperature is 200-220°C; The preparation of the inner layer melt comprises the following steps: S31, adding liquid butadiene rubber to toluene, stirring to obtain a butadiene rubber solution, adding olefin-modified carbon black to the butadiene rubber solution, and continuing to stir to obtain a mixed solution; Add the azobisisobutyronitrile solution dropwise to the mixed solution, react after the addition is complete, precipitate, filter, wash, and dry to obtain an inner layer modifier; The mass ratio of liquid butadiene rubber, toluene, olefin-modified carbon black and azobisisobutyronitrile solution is 200:(300-500):(20-30):(10-15); the reaction conditions are to react at a temperature of 65-75° C. for 6-8 hours under a nitrogen atmosphere; S32, melt-blending PETG, an inner layer modifier, SBS, an antioxidant, and a lubricant to obtain an inner layer melt; Wherein, the mass ratio of PETG, inner layer modifier, SBS, antioxidant and lubricant is (70-80):(15-20):(5-10):(0.5-1):(0.5-1), and the melting temperature is 200-220°C; Step 2: extruding the surface layer melt, the middle layer melt and the inner layer melt together in a die head, and cooling them on a cooling roller to obtain a film; Step 3: biaxially stretch the film to obtain a highly light-shielding heat-shrinkable composite film.

2. The method for preparing a highly light-shielding heat-shrinkable composite film according to claim 1, characterized in that: In the step 2, the die temperature is 240-250° C., and the thickness of the membrane is 150-250 μm.

3. The method for preparing a highly light-shielding heat-shrinkable composite film according to claim 1, characterized in that: In the step 3, the biaxial stretching is performed by firstly performing longitudinal stretching and then performing transverse stretching; The longitudinal stretching comprises preheating at 80-90°C, longitudinally stretching at 100-115°C at a ratio of 1.2-3 times in the longitudinal direction to form a film, and after longitudinal stretching to form a film, setting at 80-90°C for 2-5s; The transverse stretching comprises stretching the longitudinally stretched film after shaping at a temperature of 95-120° C. in the transverse direction at a ratio of 3-5.5 times, and shaping at a temperature of 70-95° C. after the transverse stretching, for a shaping time of 5-10 seconds.

4. A high light-shielding heat-shrinkable composite film prepared by the method for preparing a high light-shielding heat-shrinkable composite film according to any one of claims 1 to 3.